Compaction of quasi-one-dimensional elastoplastic materials - M. Reza Shaebani (Nature Portfolio, 2017)
Principles underlying crumpling of one-dimensional objects may be relevant to both biomolecular processes and to design of mechanical devices. By compacting various wires under rigid confinement and modelling observed geometric features, the authors show how friction, plasticity and torsion enhance disorder and lead to a transition from coiled to folded geometries.